Assembly of a temperature-controlled measurement system for thermoelectric materials - Yip, Weng Hou (Nanyang Technological University, 2020)
Thermoelectric properties are being explored as part of renewable energy which is vital in preserving the earth. As the technology advances, materials with thermoelectric capabilities in micro and nano scale are being explored. However, quantification of data at and beyond microscale is extremely challenging which results in scarce reliable thermoelectric data, especially for new nano materials. The objective of this project is to design a simple-to-operate system for Seebeck coefficient and resistivity measurements to determine the thermoelectric properties of micro thermoelectric devices and new nano materials. The different approaches to design, fabricate and assemble the system will be discussed in this report. This report includes the approaches to design and fabricate Device Under Test (DUT) holder that must withstand temperature of 77 – 800K operated by a temperature control unit created in this project. An AC source circuit made on a Printed Circuit Board (PCB) provides power to a microheater to generate an excitation of temperature at one extremity of DUT are discussed in this report. By the end of this project, the required number of components required for measurement of Seebeck coefficient will be known. Several experimental results for temperature control unit and Seebeck coefficient measurement made on DUT will be notable.